The use of knowledge portal: literature review/ Nur Atiqah Abdul Latif - Abdul Latif, Nur Atiqah (Faculty of Information Management, 2022)
In this pandemic era, students in higher education are facing problems of lack of information and resources in the faculty. The accessibility in acquire information from the library and other trusted institutions such as archive and museum are decreasing due to movement control order (MCO) in our country for two years now. As we know, student need to find and access the required information in through the online. Many university in our country are organized knowledge through the knowledge portal and provide many features and utilities for many users. In higher education, not only students groups are seeking the knowledge. The researchers and education staffs also are part of people that seeking knowledge for acquiring, integration and sharing the knowledge for their use. The knowledge portal are the medium of online network accessible resource through the intranet, extranet or internet with provide a simple appearance and easy to handling all the view of contents. Knowledge integration can be determined with the used of knowledge portal by the user to accessing and apply the knowledge to become more reliable and relevant sources. Although the knowledge portal have been organised and implement by university for many years, the usage of knowledge portal among the students of UiTM are being investigate in this research. Other than that, the relation between the knowledge portal use and the student performance also being investigate to determine how much impact can influence the student performance by using the knowledge portal as reference and resource in their study. The study is planned to be conducted quantitatively, where a set of questionnaire will be distributed to the target respondents. This research need to be conducted to determine any problem that can improve the knowledge portal that provided by the UiTM into more excellent platform to disseminate the knowledge. This research also can find the solution to enhance the services and utilities in the knowledge portal to attract student and user to easily use in acquiring knowledge.